Strategi Reputation Marketing untuk Mendapatkan Awareness Khalayak Radio (Studi Kasus: 97.5 Fm Motion Radio Jakarta) - Citra, Anathasia (Humaniora, 2013)
The research aims to know the implication of reputation marketing strategy in Broadcast Media Management, how the Reputation Marketing impacts the improvement of Audience awareness. This is a descriptive research using qualitative approach with the methodology of observant participatory. The result is that Reputation Marketing is essential to be conducted specially in new radio station to get attention of audiences. As the result, its increasing the awareness of the radio station and benefit for the radio station is because the increase of the numbers of advertisers.